A systematic approach to investigate the impact of nonclinical blood processing deviations on large-molecule drug bioanalysis. (February 2012) - Wang, Jin; Burns, Daniel; Ma, Mark
Jin Wang is Senior Manager of Bioanalytical Sciences at Amgen, Inc. Her main research interests are in ligand-binding assay development, method validation, method transfer, drug and biomarker bioanalysis, pharmacokinetic modeling and analysis in regulated laboratories in support of pharmacokinetic, toxicology and clinical studies for investigational new drug and biological license application filings. Wang is a member of the American Society of Pharmaceutical Scientists and a member of the Society of Quality Assurance. She is also on the 'Automation Practices in Large-Molecule Bioanalysis Harmonization Team'' of Global Bioanalysis Consortium. During nonclinical regulated toxicology studies, blood processing protocol deviations may negatively impact sample integrity and bioanalytical results. Standard practices for resolution of blood processing issues are not well established across the industry. In this article, using an illustrative example, we present a systematic approach to investigate and assess the impact of nonclinical blood processing protocol deviations that involve: assessment of the potential impact of deviations on toxicokinetic evaluation, performance of additional blood processing stability tests to ensure study sample integrity and establishment of study sample results reporting procedures to meet both scientific and regulatory quality requirements. This thorough and systematic approach can serve as a model for other analogous situations.